The complete mitochondrial genome of Mesochaetopterus japonicus (Sedentaria: Chaetopteridae) - Mei Yang; Weina Wang; Xinzheng Li; Jixing Sui (Mitochondrial DNA. Part B. Resources, 2022)
The benthic and tube-building polychaete worm Mesochaetopterus japonicus is abundantly present on the coast of the western Pacific. Here, we report the complete mitochondrial genome of M. japonicus, which is 19,326 bp in length and contains 13 protein-coding genes, 2 rRNA genes and 22 tRNA genes. All 37 genes are encoded on the heavy strand, and AT content is 70.17%. Phylogenetic analyses based on the M. japonicus mitogenome combined with previously published polychaete mitogenome data revealed that M. japonicus was closely related to Chaetopterus variopedatus and Phyllochaetopterus sp., all of which belong to Chaetopteridae. The mitochondrial genome of M. japonicus could provide useful molecular resources for further research on Polychaeta phylogeny and evolution.